Predicting Customer Loyalty of Ethnic Restaurant through Satisfaction with Marketing Mix - Sri Surjani Tjahjawati; Siti Samsiyah Purwaningsih; Sholihati Amalia (Journal of Business and Management Review, 2022)
Ethnic restaurants are the most popular restaurants in Indonesia. This study aims to analyze the effect of satisfaction with the marketing mix, namely satisfaction with the product, satisfaction with the price, satisfaction with the location, satisfaction with the promotion, satisfaction with the employee, satisfaction with the process, and satisfaction with the physical evidence on customer loyalty. The sample in this study were 200 respondents. The analysis technique used is path analysis. The results prove that satisfaction with the product, satisfaction with the price, satisfaction with the location, and satisfaction with the employee affect customer loyalty, while satisfaction with the promotion, satisfaction with the process, and Satisfaction with the physical evidence do not affect customer loyalty of ethnic restaurant. This study provides an understanding that the customer satisfaction with the marketing mix offered by ethnic restaurants will create loyalty.